2020
DOI: 10.3390/ijms21072633
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Diet in the Prevention of Chronic Diseases in Future Generations

Abstract: Nutrition is a modifiable key factor that is able to interact with both the genome and epigenome to influence human health and fertility. In particular, specific genetic variants can influence the response to dietary components and nutrient requirements, and conversely, the diet itself is able to modulate gene expression. In this context and the era of precision medicine, nutrigenetic and nutrigenomic studies offer significant opportunities to improve the prevention of metabolic disturbances, such as Type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 107 publications
(130 reference statements)
0
56
0
Order By: Relevance
“…Genetics, nutrition, and other environmental factors significantly contribute to the physiological immune and metabolic modifications occurring in pregnancy, to favor maternal adaptation to the growing and developing fetus. Maternal malnutrition adversely affects these dynamic processes by acting on the mechanisms related to the nutritional programming, including nutrition sensing signals, epigenetic regulation, gut microbiome, as well as on the nutrient-nutrient and nutrient-drug interactions, modulating maternal and fetal genes in a sex-specific manner [ 3 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetics, nutrition, and other environmental factors significantly contribute to the physiological immune and metabolic modifications occurring in pregnancy, to favor maternal adaptation to the growing and developing fetus. Maternal malnutrition adversely affects these dynamic processes by acting on the mechanisms related to the nutritional programming, including nutrition sensing signals, epigenetic regulation, gut microbiome, as well as on the nutrient-nutrient and nutrient-drug interactions, modulating maternal and fetal genes in a sex-specific manner [ 3 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current dietary recommendations promote higher intakes of fruit and vegetables and sh and PUFAs (37,38). Nevertheless, several studies over the past few years have shown that what constitutes a healthy diet for an individual depends to some extent on his or her physiology and lifestyle (39)(40)(41)(42). Individualized nutrition advice, informed by knowledge of genetic variants, are more and more favoured over standard dietary guidelines based on population-wide averages (43).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on primary cultured neurons, its neuroprotective effect has been verified on cells treated with the Aβ fragment [31][32][33][34][35].…”
Section: Genisteinmentioning
confidence: 99%
“…An interesting aspect of the matter is that, although the molecular mechanisms underlying the effect of diet on epigenetics are still poorly understood, an increasing number of innovative studies points to the exciting possibility that the effects of diet on mental health may be passed on through generations. The possibility for a dietary component to modulate non-genetic events, that still cause a potentially heritable phenotypic change, opens a sort of therapeutical route which may be helpful in the management, if not just in the control, of the disease progression [30,31]. Thus, the individual's risk of suffering from diabetes is increased if paternal grandparents have grown up in times of food abundance rather than shortage.…”
Section: Introductionmentioning
confidence: 99%